Stress and perfectionism among male and female age-specific national team players in football, handball, and ice-hockey - Sæther, S. A.; Mehus, I.; Aspvik, N. P. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
Introduction. Junior elite age-specific national players are expected to be future senior elite players. These expectations come with pressure both from the player him/herself and from significant others in their development environment. This study investigated how national team players (male and female) in football, handball, and ice-hockey in Norway experienced stressors (global score) (SG) and how the two perfectionism dimensions evaluative concerns (EC) and personal strivings (PS), as well as playing time (club), and an overload injury impact on SG. We also controlled for gender, age, sport, and playing level of the players.